A Phase II Trial Evaluating the Efficacy and Safety of Efavirenz in Metastatic Castration‐Resistant Prostate Cancer. (29th October 2014) - Houédé, Nadine; Pulido, Marina; Mourey, Loic; Joly, Florence; Ferrero, Jean‐Marc; Bellera, Carine; Priou, Frank; Lalet, Caroline; Laroche‐Clary, Audrey; Raffin, Mireille Canal; Ichas, François; Puech, Alain; et al.
Abstract : Background: Preclinical studies demonstrated that non‐nucleoside reverse transcriptase inhibitors used for the treatment of HIV could antagonize tumor development. This led us to assess the efficacy of efavirenz in patients with metastatic castration‐resistant prostate cancer (mCRPC) in a multicenter phase II study. Methods: We used a Simon two‐stage design and a 3‐month prostate‐specific antigen (PSA) nonprogression rate of 40% as a primary objective. Patients received 600 mg efavirenz daily with the possibility of a dose increase in case of PSA progression. Exploratory analyses included pharmacokinetics of efavirenz plasma concentrations and correlations with clinical outcomes. Results: Among 53 assessable patients, we observed 15 instances of PSA nonprogression at 3 months, corresponding to a nonprogression rate of 28.3% (95% confidence interval: 16.8%–42.3%). The exploratory analysis revealed that for the 7 patients in whom optimal plasma concentration of efavirenz was achieved, PSA progression was observed in only 28.6% compared with 81.8% of patients with suboptimal plasma concentrations of efavirenz. Conclusion: Although 600 mg efavirenz did not statistically improve the PSA nonprogression rate, our exploratory analysis suggests that higher plasma concentrations of this drug (i.e., use of increased dosages) may be of potential benefit for the treatment of mCRPC. Abstract : 摘要 背景 . 临床前研究证实用于治疗 HIV 的非核苷类逆转录酶抑制剂可以对抗肿瘤进展。因此我们开展了一项多中心 II 期研究以评估依非韦伦在转移性去势抵抗性前列腺癌（mCRPC）患者中的有效性。 方法 . 我们使用了 Simon 两阶段设计，主要目标是 3 个月前列腺特异性抗原（PSA）无进展率达到 40%。给予患者依非韦伦 600 mg/天治疗，如发生 PSA 进展可上调剂量。探索性分析包括依非韦伦血浆浓度的药代动力学及其与临床转归的相关性。 结果 . 3 个月时，我们在 53 例可评估患者中观察到15 例 PSA 无进展，相当于无进展率为 28.3%（95% 可信区间：16.8% ∼ 42.3%）。探索性分析显示，在 7 例达到依非韦伦最佳血浆浓度的患者中观察到的 PSA 进展率仅为 28.6%，而未达到依非韦伦最佳血浆浓度的患者 PSA 进展率达 81.8%。 结论 . 尽管依非韦伦 600 mg未能显著改善 PSA 无进展率，我们的探索性分析提示较高的血浆药物浓度（即增加给药剂量）可能为 mCRPC 的治疗带来潜在获益。 The Oncologist 2014;19:1227–1228